1986
DOI: 10.1007/bf00174068
|View full text |Cite
|
Sign up to set email alerts
|

Delta-9-tetrahydrocannabinol (THC) increases brain prostaglandins in the rat

Abstract: Intraperitoneal administration of 9-trans-delta-tetrahydrocannabinol (THC), the major psychoactive component of cannabis, in doses of 0.5, 1.0 and 2.0 mg/kg, produced a dose-related increase in the brain concentrations of prostaglandin (PG) E2 and PGF2 alpha in male rats 4 h after THC administration, as assessed by radioimmunoassay. A time-course investigation indicated that THC (2 mg/kg, IP) induced maximal increases in rat brain concentration of both PGs 2 and 4 h after administration; PG levels declined app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The present study is based upon previous work that indicate that acute administration of cannabinoids stimulates the release of arachadonic acid resulting in elevation of prostaglandins (Burstein and Hunter, 1981;Burstein et al, 1983;Laviolette and Belanger, 1986;Bhattacharya, 1986;Hunter et al, 1991). Furthermore, cannabinoids induce COX-2 expression in the central nervous system (Ramer et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…The present study is based upon previous work that indicate that acute administration of cannabinoids stimulates the release of arachadonic acid resulting in elevation of prostaglandins (Burstein and Hunter, 1981;Burstein et al, 1983;Laviolette and Belanger, 1986;Bhattacharya, 1986;Hunter et al, 1991). Furthermore, cannabinoids induce COX-2 expression in the central nervous system (Ramer et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies suggest that cannabinoids may stimulate arachidonic acid release from cultured astrocytes (24), cortical slices (25) and neuroblastoma cells (26). Additionally, ⌬ 9 -THC has been shown to increase the amount of PGE 2 in the brain (27,28). A possible interference of cannabinoids with the expression of inducible enzymes involved in arachidonic acid metabolism has been recently reported by Chan et al (29) who showed that the PG-dependent hippocampal neuronal toxicity of ⌬ 9 -THC requires de novo synthesis of mRNA and protein.…”
mentioning
confidence: 97%
“…1). Our explanation for this phenomenon is that when THC is given, [20][21][22][23][24][25] s. Indomethacin and the metaholite were each given orally in peanut oil (50 tl) 30 mm before THC. In this experiment, the pain response was measured 10 mm after THC administration.…”
Section: (-)mentioning
confidence: 99%